Assessing the efficacy of a culturally adapted cognitive-behavioural internet-delivered treatment for depression - SALAMANCA, ALICIA (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2018)
Background: Depressive disorders are the principal cause of disability in the world, with an upward trend in prevalence in low and middle-income countries (LMICs). Depression can be effectively treated, however, several barriers in Colombia affect people’s access to treatment (e.g. cost, personal stigma, limited availability of the mental health service). Internet-delivered interventions have demonstrated efficacy in high-income countries and therefore may have relevance in LMICs. Aims: To assess the efficacy of the culturally adapted cognitive behavioural internet-delivered for depression Method: The study used a mixed method approach utilising in study 1, the development of a systematic and theoretically informed approach, using quantitative and qualitative methods to assist in the cultural adaptation of the Space from Depression intervention and in study 2 a randomised control design to examine the efficacy of the culturally-adapted intervention in college students in Colombia. Study (1) involved the cultural adaptation of the Space from Depression cognitive-behavioural internet-delivered programme for depressive symptoms. The adaptation involved a cultural sensitivity framework (CSF), alongside an ecological validity framework (EVF) and principles from cross-cultural assessment research. This includes initial researcher/clinician adaptation and the integration of cultural assessment feedback of the programme by a panel of experts and users using the theoretically-based Cultural Relevance Questionnaire (CRQ). Study (2) consisted of the implementation of the culturally adapted intervention using a randomised controlled design. The efficacy trial included an internet-delivered cognitive behavioural therapy (iCBT) group and a waiting list (WL) control group of participants meeting eligibility criteria (mild to moderate depressive symptoms). The active condition consisted of 7 weekly modules of CBT Space from Depression, with post-session feedback from a trained supporter. The primary outcome included the Patient Health Questionnaire (PHQ-9). The study also involved a collection of client reported significant events and client satisfaction with the internet-delivered treatment. Results: In study 1 the adaptation included the following stages: a) establishment of CSF, which included the incorporation of Colombian cultural expressions; b) Users’ (n=5) and experts’ (n=7) evaluation (EVF), based on cross-cultural assessment principles; c) cultural incorporations into the programme. The CRQ was developed and used by users and experts to evaluate the intervention. The CRQ demonstrated good reliability in the sample (Cronbach’s Alpha 0.744). Qualitative analysis supported the culturally sensitive changes made to the programme, such as personal stories and textual translations from English and these were considered ecologically valid and representative. In study 2, 214 college students were recruited from two cities in Colombia (107 iCBT group and 107 WL control group). Repeated measures within group showed significant reductions in depressive symptoms. Linear mixed model (LMM) including fixed effects for time showed significant effects post-treatment (t=-5.189, df=197.54, p=<0.00) and these effects were maintained into 3-months follow up (t=4.668, df=39.62, p=<0.000). The results show that the users report positive experiences using the culturally adapted programme and satisfaction with the treatment. A noted limitation of the work is that the research attrition was high. Conclusions: The study sought to establish a theoretically robust methodology for culturally adapting internet-delivered interventions for mental health disorders and to evaluate the efficacy of a culturally adapted internet-delivered treatment for depression in Colombia, with support. The study is the first contribution to a method for culturally adapting internet-delivered interventions and also a first to examine the efficacy of such an adapted intervention in Latin America
APPROVED
Keywords: Culturally adapted psychotherapy, Internet-delivered treatment, Depressive symptoms, CBT, College students, South America, randomised control trial